2019
DOI: 10.1021/acs.orglett.9b00973
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Imidazolidinone, Imidazolone, and Benzimidazolone Derivatives through Oxidation Using Copper and Air

Abstract: A new synthetic method of urea derivatives using copper and air was developed. These mild conditions provided moderate to very good yields for 15 examples (53-93%), while low yields were obtained with sterically hindered substrates (3 examples). The reaction was found to go through an in situ-generated copper-N-heterocyclic carbene, which is then oxidized into cyclic urea derivatives possessing alkyl, benzyl, aryl, hydroxy, Boc-protected, and tertiary amine groups. compounds will be disclosed in due course. AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Oxidation of M/NHC complexes 51 , leading to formation of O–NHC bond and affording imidazoline-2-ones 52 or related substances, certainly deserves attention. 172 , 181 , 182 , 222 For example, homogeneous aerobic oxidation of Cu I /NHC complexes can be used for preparative synthesis of cyclic ureas ( Scheme 11 ). 181 The reaction is highly sensitive to the NHC steric bulkiness and possibly includes a reductive elimination step.…”
Section: Organometallic Chemistry Behind the H–nhc C–nhc And X–nhc Cmentioning
confidence: 99%
“…Oxidation of M/NHC complexes 51 , leading to formation of O–NHC bond and affording imidazoline-2-ones 52 or related substances, certainly deserves attention. 172 , 181 , 182 , 222 For example, homogeneous aerobic oxidation of Cu I /NHC complexes can be used for preparative synthesis of cyclic ureas ( Scheme 11 ). 181 The reaction is highly sensitive to the NHC steric bulkiness and possibly includes a reductive elimination step.…”
Section: Organometallic Chemistry Behind the H–nhc C–nhc And X–nhc Cmentioning
confidence: 99%
“…These results strongly indicate that Y contains the same azolium cation (NHC•H + ) as 4b . Recently, Ollevier observed that treatment of a NHC•CuX complex with atmospheric air in CH 2 Cl 2 afforded the corresponding hydrolysis product such as an azolium compound [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that this reaction pathway differs from previous methods involving an imidazolium salt. [6][7][8][9] The N-methyl benzimidazole 1 a did not furnish the required benzimidazolone in the absence of alkyl halide under standard conditions (Scheme 2, eq. 3).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the oxidation of imidazolium salts using strong oxidants has proven to be an effective pathway to imidazolones (Scheme a) . Ollevier and colleagues recently demonstrated that imidazolidinone, imidazolone, and benzimidazolone derivatives could be synthesized efficiently via the oxidation of imidazolium salts using a copper catalyst and air as an oxidant at room temperature . However, this route requires the initial synthesis of imidazolium salts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation